Saudi Arabian expatriate worker fitness-screening programme: a review of 14 years of data/Programme Saoudien d'evaluation des aptitudes physiques des travailleurs expatries: examen de 14 annees de donnees - Alswaidi, F.M; Memish, Z.A; Al-Hakeem, R.F; Atlam, S.A (Eastern Mediterranean health journal, 2013)
Expatriate workers must be medically examined in their country of origin at accredited centres prior to their arrival in any Gulf Cooperation Council (GCC) country and are reexamined when they enter the country. This review investigated the epidemiological profile of registered expatriate workers in Saudi Arabia who were found medically unfit to work. A descriptive analysis was performed on 4 272 480 records of a Ministry of Health database from 1997 to 2010. The greatest proportion of workers was from Indonesia (34.3%). The total proportion of unfit expatriate workers was low (0.71%). The highest rate of unfitness was among workers from Ethiopia (4.06%), followed by Somalia (2.41%). Hepatitis B infection was the most common cause (57.5%), followed by noncommunicable diseases (21.2%) and hepatitis C infection (17.4%). This review suggests that the total number of workers registered in the Saudi Ministry of Health was underestimated, and the rate of unfit workers was lower than for other GCC countries, suggesting that standards and quality assurance in Saudi laboratories require revision. Les travailleurs expatries doivent passer une visite medicale dans leur pays d'origine, dans un centre accredite avant leur arrivee dans un pays du Conseil de cooperation du Golfe, et sont ensuite reexamines sur place. Le present examen portait sur le profil epidemiologique des travailleurs expatries enregistres en Arabie saoudite qui avaient ete declares medicalement inaptes au travail. Une analyse descriptive de 4 272 480 dossiers, issus d'une base de donnees du ministere de la Sante, entre 1997 et 2010 a ete realisee. La plus importante part des travailleurs venait d'lndonesie (34,3 %). La proportion totale de travailleurs expatries inaptes etait faible (0,71 %). Le taux d'inaptitude le plus eleve a ete observe chez les travailleurs ethiopiens (4,06 %), et somaliens (2,41 %). L'infection par le virus de l'hepatite B etait la cause la plus frequente (57,5 %), suivie par les maladies non transmissibles (21,2 %) et l'infection par le virus de l'hepatite C (17,4 %). Cette analyse semble indiquer que le nombre total de travailleurs enregistres au ministere de la Sante saoudien etait sous-estime et que le taux de travailleurs inaptes est inferieur a celui des autres pays du Conseil de cooperation du Golfe, ce qui donne a penser qu'une revision des normes et de l'assurance qualite des laboratoires saoudiens est necessaire.